The Role of Environmental Turbulence on Firm Innovativeness: Evidence from Small and Medium Enterprises in Nigeria - Baba, Mukhtar; Audu, Ibrahim (Kashere Journal of Management Sciences, 2024)
It is generally agreed that innovation is critical to firm competitive advantage. This study Examine the relationship between environmental turbulence and SMEs innovativeness in Kano Nigeria. SMEs are regarded as an important ingredient in the economic growth of nations and especially so in developing nations such as Nigeria. Accordingly, a sample of 320 SMEs aged between 5 to 20 years from four different sectors participated in the study. Moreover, Structural Equation Modelling (using Smart PLS) approach was applied to assess the measurement model and the relationships between the constructs. Consequently, the findings shows that environmental turbulence (as measured by Technological and demand/Market Turbulence) have positive effect on SMEs ability to innovate.The research expand the innovation literature by confirming the influence of environmental turbulence on SMEs innovativeness in a developing nation (Nigeria). To be precise, the results from this research reveals that the degree of organisational innovativeness for SMEs tends to increase and therefore should be supported in environments with greater technological and market/ demand turbulence. Moreover, this finding will help managers of SMEs on how to improve their firms’ ability to innovate in their respective organizations.